Compact and tunable stretch bioreactor advancing tissue engineering implementation. Application to engineered cardiac constructs. (October 2020) - Putame, Giovanni; Gabetti, Stefano; Carbonaro, Dario; Meglio, Franca Di; Romano, Veronica; Sacco, Anna Maria; Belviso, Immacolata; Serino, Gianpaolo; Bignardi, Cristina; Morbiducci, Umberto; Castaldo, Clotilde; Massai, Diana
Highlights: Compact, easy-to-use, tunable stretch bioreactor. Validation tests confirmed the bioreactor accuracy, repeatability and reliability. Biological tests demonstrated bioreactor suitability for cardiac tissue engineering applications. Cyclic stretch promoted human cardiac progenitor cells differentiation towards adult cardiac myocytes. Abstract: Physical stimuli are crucial for the structural and functional maturation of tissues both in vivo and in vitro . In tissue engineering applications, bioreactors have become fundamental and effective tools for providing biomimetic culture conditions that recapitulate the native physical stimuli. In addition, bioreactors play a key role in assuring strict control, automation, and standardization in the production process of cell-based products for future clinical application. In this study, a compact, easy-to-use, tunable stretch bioreactor is proposed. Based on customizable and low-cost technological solutions, the bioreactor was designed for providing tunable mechanical stretch for biomimetic dynamic culture of different engineered tissues. In-house validation tests demonstrated the accuracy and repeatability of the imposed mechanical stimulation. Proof of concepts biological tests performed on engineered cardiac constructs, based on decellularized human skin scaffolds seeded with human cardiac progenitor cells, confirmed the bioreactor Good Laboratory Practice compliance and ease of use, and the effectiveness of the delivered cyclic stretch stimulation on the cardiac construct maturation.